Thermal Analysis and Structural Optimization of High-Efficiency Fuel Submersible Hot Water Machine - Zhaozhe Zhu; Youmin Wang; Yingshuai Zhang (Advances in Materials Science and Engineering)
Based on the oil quality of diesel oil, the thermal efficiency and fuel consumption of the fuel-burning submersible hot water machine were calculated. The structure of the fuel-burning submersible hot water machine was designed. The heat transfer calculation of the flame tube and convection surface of the high-efficiency fuel submersible hot water machine was carried out, and the overall heat balance of the system was checked. ANSYS was used to analyze and study the mechanical and thermodynamic properties of the fuel-based submersible hot water machine, and the simulation results were compared with the theoretical calculation results. The thermal field of the flame tube and the threaded tube was simulated, and the influence of the temperature field on the flame tube was analyzed. The changes in the total deformation and strength of the flame tube under the thermal structure coupling were studied. The thermal efficiency of oil-fired submersible hot water machine was studied, and the relevant factors affecting the thermal efficiency of oil-fired submersible hot water machine were put forward. The main factors affecting thermal efficiency were analyzed and mathematically modeled. The air supply model and the convective heat transfer model of the threaded tube were established. The main parameters that affected the thermal efficiency of the threaded tube were optimized. In the end, the design scheme of a high-efficiency fuel-type submersible hot water machine was obtained.